Analysis of Emotional Representation through Characters in the Inside Out 2 Movie Poster Using Charles Peirce’s Semiotic Approach - Dessy Fitriani; Novi Rahmawati; Rafli Al-Qadar; Aliyah Aliyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Film posters serve as crucial visual communication media capable of conveying complex emotional messages through visual elements. This research aims to analyze the visual representation of emotions in the Inside Out 2 movie poster, focusing specifically on the newly introduced secondary emotions such as Anxiety, Ennui, Embarrassment, and Envy, which portray the psychological transition of adolescence. Utilizing Charles Sanders Peirce's semiotic approach, this study employs a descriptive qualitative method to categorize visual elements into icons, indexes, and symbols. The findings reveal that the anthropomorphism of these abstract emotions is accurately represented through specific anatomical disproportions (icons), gestures and attributes indicating psychological states (indexes), and deliberate color palettes conveying social conventions and emotional warnings (symbols). Furthermore, the vertical hierarchical layout visually simulates the disruption and dominance of secondary emotions over primary emotions within the teenage mind's control center. The visual structure effectively translates internal psychological conflicts into a communicative two-dimensional medium. This study provides a profound understanding of how visual design elements in animation posters function beyond aesthetics, acting as complex sign systems that communicate psychological dynamics to the audience.